The relationship between patients with Multiple Sclerosis’ needs for education and consultation in pharmacy in order to the use of injectable drugs and management of related adverse drug reactions, and the errors found in their answers to the questions in - Aliaghdam, Fatemeh (International Pharmacy Acta, 2018)
Multiple sclerosis (MS) is the most common inflammatory disease of the central nervous system, and is the main cause of impotence in young adults. In the last decade, the epidemiology of this disease in Iran has been a very important issue and its prevalence is increasing rapidly. The chronic nature of the disease makes it very difficult for patients to adhere to treatment. And intolerance or discontinuation of treatment can result in higher rates of inability and increased hospitalization, and those who remain under treatment are less likely to have recurrence or disease progression. It is still not a cure for the disease, and moderating treatments are used from the 90's to the present. The most important causes and barriers to treatment in these patients are problems with injection and side effects. The problems of injection are one of the biggest dams known in these patients, such as forgetfulness of injection, being dependent on others, anxiety during injection. Drug side effects are also another issue for patients admitting drugs that discontinue treatment, dose adjustment, or drug therapy. Introduction: Accordingly, in this study, patients' information is the source of their information and how they are used and maintained and managed by them, which is to identify the essential aspects of educational and counseling to cover the needs of these patients by evaluating their mistakes in the fields of They will be examined and their comments on what they need to be informed or consulted. Method and results: This cross-sectional study was performed on patients with MS. Referring to a supermarket pharmacy on November 13th. Supermarket Drugstore, November 13, one of the reference pharmacies for delivery of MAS drugs. It should be. Information in this study is collected by a self-administered questionnaire and information from a patient in the pharmacy. Multiple sclerosis is a central nervous system disorder that affects young people, those who are genetically more susceptible and who live in specific geographical contexts. Although the exact etiology is unknown, it is an autoimmune disorder caused by an agent or agents The environment is flammable. This disease does not have complete recovery, but by controlling symptoms, it can improve the quality of life of the affected patients, and can be suppressed by some of the current treatments. conclusion: The average level of women's information about MS and injections is significantly higher than that of men. Also, the information of MS people living in Tehran and the suburbs is far more than those living in the counties. And the information of educated people is significantly different from those who are illiterate and below There is no diploma. The main reason for the discontinuation of MS medications is its drug-induced side effects, which interfere with everyday life and activities of individuals.